Green infrastructure: a new strategy for stormwater management In downtown Wichita - Johnson, Aaron (Kansas State University, 2013)
Wichita is an historic keystone in American history. Since 2002, Wichita has begun another period of urbanization and the Wichita Downtown Development Corporation (WDDC) was formed to help facilitate the needs of both the people wanting to move downtown and the developers who aim to realize the city’s historic potential. With the help of the WDDC the City of Wichita adopted the Project Downtown Master Plan developed by the Boston based firm Goody Clancy in 2010. The Project Downtown has a market driven development strategy that has little concern for ecology. The economically driven master plan gives little reason for a developer to be ecologically and socially oriented. The City of Wichita does have a rudimentary incentive focused on public infrastructure. Essentially, the City of Wichita will front the money to help develop the public infrastructure of a site to ease the total development costs. This is the key to begin defining the Project Downtown’s green spaces that are socially and ecologically oriented. Green infrastructure is a method of developing land used by pedestrian, automobile, and other human needs in a way that is ecologically sensitive. The general idea of green infrastructure is to open up the barrier of an impermeable infrastructure created by urban development to the soil below. The goal is to get as close to an undeveloped footprint as possible while still meeting the needs of the humans who occupy the area. This project looks at the Catalyst Site C-2 (chosen by the Project Downtown as an integral step of development) and designs the given program using several green infrastructure techniques. The proposed design is treated as a pilot project intended to treat 80% of the stormwater runoff developed by the building, automobile, and pedestrian space during a two year, one hour storm. This schematic design would cost roughly $536,00 designed using traditional grey infrastructure of impervious pavements that drain directly to the Arkansas River. By implementing green infrastructure the costs total roughly $533,000 saving $4,000 and greatly improving the ecological and social benefits of the design.
Keywords: Landscape architecture; Landscape performance; Downtown development; Cost analysis; Economic development; Green infrastructure; Landscape Architecture (0390)